Profil Istitha’ah Kesehatan Pada Jamaah Haji Kota Palu pada Tahun 2019 - Lutfiah Sahabuddin; Irfan Nahwi Rasul (Lembaga Layanan Pendidikan Tinggi (LL-DIKTI) Wilayah IX Sulawesi, 2020)
Pilgrimage is the fifth pillar of Islam which is a once-in-a-lifetime obligation for every Muslim who is able to fulfill it. In the Alqu'an Surah Al Imran verse 97 it is explained that doing Hajj is a human obligation towards Allah, namely (for) those who are able (istitha'ah) to travel to the Baitullah. Thus, istitha'ah is an important thing in the implementation of the pilgrimage, which in Islamic fiqih, Istitha'ah (including Istitha'ah Health) is stated as one of the mandatory requirements for carrying out the Hajj. This study aims to determine the profile of the health status of the Candidates for Hajj Hajj in Palu City 2019. The research method used was descriptive observational and data collection methods were carried out by total sampling with a total of 770 samples. The results obtained in this study are the profile of the health istitha'ah Candidates for Hajj Pilgrims in Palu City 2019, the highest in Istitha'ah Fulfills the Health Requirements for Hajj as many as 433 Candidates for Hajj (56.2%), Istitha'ah fulfills Hajj health with 332 CJH assistance (43.1%), do not meet the requirements for Hajj Health Istitha'ah while as many as 5 CJH (0.6%), and do not meet the Istitha'ah Hajj Health Requirements as many as 0 samples (0%).